Evaluation of the Accuracy and Precision of a Next Generation Computer-Assisted Surgical System - Angibaud, Laurent D. (Clin Orthop Surg, 2015)
BACKGROUND: Computer-assisted orthopaedic surgery (CAOS) improves accuracy and reduces outliers in total knee arthroplasty (TKA). However, during the evaluation of CAOS systems, the error generated by the guidance system (hardware and software) has been generally overlooked. Limited information is available on the accuracy and precision of specific CAOS systems with regard to intraoperative final resection measurements. The purpose of this study was to assess the accuracy and precision of a next generation CAOS system and investigate the impact of extra-articular deformity on the system-level errors generated during intraoperative resection measurement. METHODS: TKA surgeries were performed on twenty-eight artificial knee inserts with various types of extra-articular deformity (12 neutral, 12 varus, and 4 valgus). Surgical resection parameters (resection depths and alignment angles) were compared between postoperative three-dimensional (3D) scan-based measurements and intraoperative CAOS measurements. Using the 3D scan-based measurements as control, the accuracy (mean error) and precision (associated standard deviation) of the CAOS system were assessed. The impact of extra-articular deformity on the CAOS system measurement errors was also investigated. RESULTS: The pooled mean unsigned errors generated by the CAOS system were equal or less than 0.61 mm and 0.64° for resection depths and alignment angles, respectively. No clinically meaningful biases were found in the measurements of resection depths (< 0.5 mm) and alignment angles (< 0.5°). Extra-articular deformity did not show significant effect on the measurement errors generated by the CAOS system investigated. CONCLUSIONS: This study presented a set of methodology and workflow to assess the system-level accuracy and precision of CAOS systems. The data demonstrated that the CAOS system investigated can offer accurate and precise intraoperative measurements of TKA resection parameters, regardless of the presence of extra-articular deformity in the knee.